ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI AKSESIBILITAS UMKM TERHADAP PRODUK PEMBIAYAAN DI BANK UMUM SYARIAH (Studi Pada Kecamatan Pamijahan Kabupaten Bogor, Jawa Barat) - Anita; Tubagus Rifqy Thantawi; Ermi Suryani (Jurnal Penelitian Perbankan Syariah: Program Studi Perbankan Syariah., 2021)
ABSTRACT In Indonesia, Micro, Small and Medium Enterprises (MSMEs) have an important role as the backbone of the Indonesian economy. In developing their business, SMEs are faced with several problems. Among them are low human resources, limited facilities and infrastructure, technology, the main factors that hinder the development of MSMEs are the lack of capital and limited access to finance. The MSME development process automatically requires a lot of funding, so many MSMEs finance through bank loans. This study aims to analyze the factors of education level, business experience, business turnover, compliance with paying income tax, total assets and type of business to affect the accessibility of MSMEs to financing products in Islamic banks. This type of research is quantitative research, taking a sample of 150 respondents using the Tabachic & Fidell technique, the sampling technique using simple random sampling technique. Methods of data analysis using multiple linear regression. The results of the t test showed that each independent variable, namely education level, business experience, had no positive and significant effect. Meanwhile, business turnover, compliance with paying income tax, total assets and type of business partially have a positive and significant effect. The results of the F test indicate that there is a positive influence simultaneously between the variables of education level, business experience, business turnover, compliance with paying income tax, total assets and type of business on accessibility.